2022
DOI: 10.1371/journal.ppat.1010102
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae requires oxidative respiration through the bd-I and cbb3 oxidases for intestinal proliferation

Abstract: Vibrio cholerae respires both aerobically and anaerobically and, while oxygen may be available to it during infection, other terminal electron acceptors are proposed for population expansion during infection. Unlike gastrointestinal pathogens that stimulate significant inflammation leading to elevated levels of oxygen or alternative terminal electron acceptors, V. cholerae infections are not understood to induce a notable inflammatory response. To ascertain the respiration requirements of V. cholerae during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…is hypoxic/anaerobic, despite animal experiments that suggest aerobic respiration in the upper gastrointestinal tract is important for infection [41,42]. Using minimum inhibitory concentration (MIC) assays, we found that AMR increased under anaerobic conditions for select antibiotics, and novel genetic targets for AMR were discovered under anaerobic conditions.…”
Section: Impact Statementmentioning
confidence: 92%
“…is hypoxic/anaerobic, despite animal experiments that suggest aerobic respiration in the upper gastrointestinal tract is important for infection [41,42]. Using minimum inhibitory concentration (MIC) assays, we found that AMR increased under anaerobic conditions for select antibiotics, and novel genetic targets for AMR were discovered under anaerobic conditions.…”
Section: Impact Statementmentioning
confidence: 92%
“…Previous studies have shown that V. cholerae relies on standard carbon metabolism pathways coupled with oxygen respiration in the host, including the Embden-Meyerhof-Parnas (glycolysis) and Entner-Doudoroff pathways [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate metabolism is an essential aspect of V. cholerae pathogenesis. Previous studies have shown that V. cholerae relies on standard carbon metabolism pathways coupled with oxygen respiration in the host, including the Embden-Meyerhof-Parnas (glycolysis) and Entner-Doudoroff pathways 3436 . Recent studies demonstrate that pyruvate dehydrogenase and pyruvate formate lyase, enzymes that facilitate the transition to T.C.A.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the high respiration rate at their normal harvesting season, sweet cherries deteriorate rapidly, resulting in the loss of flavor, pedicel browning, and decay (Wang & Long, 2014; Yang et al, 2019). Respiration under aerobic or anaerobic conditions supplies energy and substrates to ensure cells to carry out essential metabolism (Van Alst et al, 2022). However, metabolic substrates are consumed during respiration that affect the quality of fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%